Influence of multipolar magnetic field geometry of ECR planar plasma source on plasma parameters - Fedorchenko, V.D.; Chebotarev, V.V.; Garkusha, I.E.; Medvedev, A.V.; Tereshin, V.I.; Shevchuk, B.A. (Вопросы атомной науки и техники, 2008)
The plasma parameters and its homogeneity were measured in ECR planar plasma source with multipolar magnetic field, which is created by three parallel magnetic bars of 12 cm in length consisted of set of the permanent magnets of 2 cm length. Geometry of the multipolar magnetic field is able to be changed by variation of the polarity and the distance between separate magnets along the bars. For magnetic system with alternative orientation of the magnetic field the plasma density up to 2.8×10¹⁰ сm¯³ and the electron temperature about 20-22 eV were measured within the area ~ 75 cm² at the distance of 2 cm apart the magnetic structure. The uncompensated ion flow with the energies of 16-18 eV was observed for all configurations of magnetic field. Параметри плазми та її однорідність були виміряні у планарному ЕЦР-плазмовому джерелі із мультипольним магнітним полем, яке утворювалося паралельними магнітними стрижнями довжиною 12 см, що складались з окремих постійних магнітів по 2 см кожний. Геометрія мультипольного магнітного поля змінювалася за рахунок варіювання полярності окремих магнітів та відстані між ними вздовж стрижня. Для магнітної системи з перемінною орієнтацією магнітного поля магнітів вздовж стрижня та с зазором 0,8 см між ними густина плазми складала 2.8×10¹⁰ сm¯³ та електронна температура 20-22 еВ. Показана однорідність параметрів плазми на площині ~ 75 cm² на відстані 2 см від магнітної структури. Для усіх конфігурацій магнітного поля спостерігався некомпенсований потік іонів з енергією 16-18 еВ. Измерены параметры плазмы и их однородность в планарном ЭЦР- плазменном источнике с мультипольным магнитным полем, которое создавалось параллельными магнитными стержнями длинной 12 см, состоящих из отдельных постоянных магнитов по 2 см каждый. Геометрия мультипольного магнитного поля изменялась за счет выбора полярности отдельных магнитов и расстояния между ними вдоль магнитного стержня. Для магнитной системы с переменной вдоль стержня ориентацией магнитного поля магнитов и с зазором 0,8 см между ними плотность плазмы составила 2.8×10¹⁰ сm¯³ и электронная температура 20-22 эВ. Показана однородность параметров плазмы на площади ~ 75 cm² на расстоянии 2 см от магнитной структуры . Для всех конфигураций магнитного поля наблюдался некомпенсированный поток ионов с энергией 16-18 эВ.